Concepções de alfabetização científica reveladas por graduandos de um curso de pedagogia - Matheus, Ilda Felix (2019)
This research is inserted in the area of Natural Sciences Teaching (ECN) focusing on the relations between Science, Technology and Society (CTS), especially on the Scientific Literacy (AC) of the citizens, considering the new challenges for the century XXI in terms of education, for the critical formation of citizens and their participation in social and scientific decisions in the social environment in which they are inserted. We sought to investigate the conceptions of Pedagogy students about Scientific Literacy. The 2017 Common National Curriculum Base (BNCC) emphasizes Scientific Literacy (LC) as the application of knowledge acquired from Scientific Literacy (CA), which justifies this research. The objective was to know the conceptions of students of Pedagogy, future teachers of the early years of Elementary School, about Scientific Literacy (AC). The research was guided by the qualitative approach of the Content Analysis type. As a data collection instrument, a semi-structured questionnaire was used, aiming to know the profile of the students of a Pedagogy course, as well as their conceptions about the subject. The described and discussed data analysis revealed a lack of systematized knowledge about CA. However, it was noticed that the little knowledge revealed by the students about CA presents an approximation with the theories of the authors referenced in this research, especially with Structuring Axes and the Scientific Literacy Indicators proposed by Sasseron. The analysis also revealed that students associate the teaching / learning processes and methodologies of science teaching with CA. This inference is justified by the fact that these themes are studied in disciplines that are part of the curriculum of the Pedagogy Degree course of the institution where the research was conducted. From the results that evidenced the lack of systematized knowledge about CA, the need of reflection on the curricula of Pedagogy courses is emphasized, considering the possibility of including the CA theme in a discipline in the area of Natural Sciences.